Crossing Streams in the Dark: Religious Pluralism and Theological Education. Issue 3 (September 2016) - Payne, Richard K.
Abstract: Examining a presentation made to the Pacific Coast Theological Society in 1939, this essay identifies some of the enduring issues for theological and religious education created by the reality of religious pluralism. Addressing religious pluralism is a dialectic process moving between the two poles of disorienting otherness and analogies based on the already familiar. Both moments are necessary, and neither is final. Education in a religiously plural world requires enabling students to live in a state of uncertainty.